2018
DOI: 10.18844/gjpr.v8i2.3490
|View full text |Cite
|
Sign up to set email alerts
|

Screening for the hyperkinetic disorder by using strength and difficulties questionnaire teacher-report (SDQ-TR) in Indonesia school-aged children

Abstract: The aim of the research was to examine the validity of strength and difficulties questionnaire teacher-report (SDQ-TR) to screen hyperkinetic disorder in Indonesia school-aged children. The SDQ-TR was administrated to the teacher of representative samples of 222 elementary school children (7-14 years old). The SDQ-TR hyperactivity-inattention subscale scores were compared with the clinical diagnostic classification from clinical psychologists. The validity of the screening result was analysed using receiver op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The questionnaire used by the researcher was the Strength and Difficulty Questionnaire in Children (SDQ) which was used to measure behavior problems in children. The psychometric quality in Strength and Difficulty Questionnaire Indonesia Version has been analysed, including the self-report version (Istiqomah, 2017;Wiguna & Hestyanti, 2012) and the teacher report version (Oktaviana & Wimbarti, 2014;Siregar & Wimbarti, 2018). SDQ has been adapted in various languages and it is used in many countries, including Arabic (Hariz et al, 2013), Australia (Hawes & Dadds, 2004), the Netherlands (Mieloo et al, 2012), China (Mellor et al, 2016), Japan (Tanabe et al, 2013), Germany (Petermann, Petermann, & Schreyer, 2010), Spain (Ortuño -Sierra, Aritio-Solana, & Fonseca-Pedrero, 2018), Sweden (Smedje, Broman, Hetta, & von Knorring, 1999), Taiwan (Liu et al, 2013).…”
Section: Data Collection Techniquementioning
confidence: 99%
“…The questionnaire used by the researcher was the Strength and Difficulty Questionnaire in Children (SDQ) which was used to measure behavior problems in children. The psychometric quality in Strength and Difficulty Questionnaire Indonesia Version has been analysed, including the self-report version (Istiqomah, 2017;Wiguna & Hestyanti, 2012) and the teacher report version (Oktaviana & Wimbarti, 2014;Siregar & Wimbarti, 2018). SDQ has been adapted in various languages and it is used in many countries, including Arabic (Hariz et al, 2013), Australia (Hawes & Dadds, 2004), the Netherlands (Mieloo et al, 2012), China (Mellor et al, 2016), Japan (Tanabe et al, 2013), Germany (Petermann, Petermann, & Schreyer, 2010), Spain (Ortuño -Sierra, Aritio-Solana, & Fonseca-Pedrero, 2018), Sweden (Smedje, Broman, Hetta, & von Knorring, 1999), Taiwan (Liu et al, 2013).…”
Section: Data Collection Techniquementioning
confidence: 99%
“…As indicated by many studies of SDQ in various countries, the cut-off scores in different countries is influenced by its local culture. Report from Siregar and Wimbarti (2018) investigating SDQ-Teacher Report revealed diagnosis consistency of hyperkinetic analyzed using receiver operating characteristic (ROC), likelihood ratio (LR) and Chi-Square indicated of ROC and LR cutoff point ≥ 7, obtained prevalence of hyperkinetic disorder equals to 34.23% with sensitivity 72.4% and specificity 73.3%. Positive and Negative LR were 2.71 and 0.38.…”
Section: Study Of Sdq-pr and Sdq-sr In Thementioning
confidence: 99%
“…Preliminary interview with three primary school teachers in the Special District of Yogyakarta, Indonesia showed that, despite its importance, teachers still struggle to detect ADHD. They found the detection method to be unfamiliar, causing them to experience difficulties in conducting extensive observation (Siregar & Wimbarti, 2018). For that reason, it is common for children with ADHD to receive little attention from the teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we conducted clinical adaptation of The Strength and Difficulties Questionnaire, Teacher Reports (SDQ-TR) to detect behavioral and hyperkinetic disorders (Siregar & Wimbarti, 2018). The finding showed that SDQ-TR, which used Pedoman Penggolongan Diagnosis Gangguan Jiwa (Mental Disorder Diagnosis Classification Guidelines, or PPDGJ III) as the standard to conduct the diagnosis, was sensitive and specific in measuring behavioral and hyperkinetic disorders.…”
Section: Introductionmentioning
confidence: 99%